Technology and Communication Considerations for Engaging Youth Receiving Supplemental Security Income (SSI) Benefits: Vocational Rehabilitation Counselor Perspectives. (October 2021) - Anderson, Catherine A.; Brinck, Emily A.; Trainor, Audrey; Schlegelmilch, Amanda; Roskowski, Matthew; Hartman, Ellie
Technology has been shown to enhance daily activities, increase participation in individualized planning and supports, and accommodate the transition needs of students with disabilities. This study examined the benefits and challenges regarding technology use when providing transition services for youth and families receiving Supplemental Security Income (SSI) benefits. Specifically, it explored the nuances of employing technology to encourage engagement in Wisconsin Promoting the Readiness of Minors in Supplemental Security Income (WI PROMISE) services and foster communication between counselors and participants. This qualitative study used a constant comparative method for analyzing data collected through two focus groups of WI PROMISE counselors. Counselors identified technology as essential to maintaining contact with WI PROMISE participants as well as extant barriers including inconsistent access to the internet, financial expense, and insufficient training and support. Recommendations for using technology to communicate with transition-age youth and their families will be discussed.